Respuesta :

Answer:

[tex]1) \: {a}(2) = {a}(1) + 6 \\ = 14 \\ \\ {a}(3) = {a}(2) + 6 \\ =20 \\ {a}(4) = {a}(3) + 6 \\ = 26[/tex]

[tex]2) \: a(2) = a(1) + 2 \\ = - 2 \\ a(3) = a(2) + 2 \\ = 0 \\ a(4) = a(3) + 2 \\ = 2[/tex]

[tex]3)a(2) = 4 \times a(1) - 2 \\ = 28 - 2 \\ = 26 \\ a(3) = 4 \times a(2) - 2 \\ = 104 - 2 \\ = 102 \\ a(4) = 4 \times a(3) - 2 \\ = 408 - 2 \\ = 406[/tex]

[tex]4)a(2) = 2 \times a(1) + 5 \\ = - 10 + 5 \\ = - 5 \\ a(3) = 2 \times a(2) + 5 \\ = - 10 + 5 \\ = - 5 \\ a(4) = 2 \times a(3) + 5 \\ = - 10 + 5 \\ = - 5[/tex]

[tex]5) - 6 - ( - 4) \\ = - 6 + 4 \\ = - 2 \\ \\ a(n) = a(n) - 2 \\ a(1) = - 4[/tex]

i think this is it!? not sure tho